Pelatihan Permainan Tradisional Sunda Manda Sebagai Media Etnomatematika Dan Motorik AUD - Asyura, Ira; Supriadi, Idris; Jannah, Rihatul; Maarif, Minhatul; Linda, Linda; Munawar, Badri; Kamali, Asep Saefullah (LPPM UNINUS, 2023)
Children's ability to explore their knowledge through play will optimize children's growth and development because through play children gain their own learning experiences. Teachers must have broad insight into developing what is around them to use as games, one of which is using traditional games in learning. This community empowerment activity aims to increase the knowledge and skills of Kindergarten/RA teachers to recognize and utilize traditional games as a medium for learning mathematics, aspects included in early childhood motor development, both fine and gross motor skills and their evaluation in learning, as well as encouraging kindergarten/RA teachers to be creative in creating fun mathematics learning at an early age by learning while playing. The community service carried out takes a community-based empowerment scheme, where the communities used as partners are non-productive. The partner in this activity is the Raudhatul Athfal Teachers Association (IGRA) in the Cikedal sub-district. The implementation method that will be carried out is a) preparing tools in the form of Sunda Manda traditional game puzzle; b) conducting FGD preparation for training; c) implementation training; and d) implementation in learning. The results after carrying out this service activity were that the teacher was very enthusiastic about listening to the presentation of material from the resource person, and the teacher was very cheerful when carrying out a game simulation accompanied by STKIP student Syekh Manshur. The implication after carrying out this activity is that there is a relationship between memory and motor development. Therefore, the Sunda Manda traditional game is very appropriate to be used as an ethnomathematics medium that introduces mathematical material through culture, and a medium for early childhood motoric development.